2017
DOI: 10.1016/j.neuropharm.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

CRF modulates glutamate transmission in the central amygdala of naïve and ethanol-dependent rats

Abstract: Corticotropin-releasing factor (CRF) signaling in the central nucleus of the amygdala (CeA) is hypothesized to drive the development of alcohol dependence, as it regulates ethanol intake and several anxiogenic behaviors linked to withdrawal. Excitatory glutamatergic neurotransmission contributes to alcohol reinforcement, tolerance and dependence. Therefore, in this study we used in vitro slice electrophysiology to investigate the effects of CRF and its receptor subtype (CRF1 and CRF2) antagonists on both evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…CRF has also been shown to alter excitatory transmission within the CeA. CRF application reduced evoked glutamate responses and enhanced glutamate release in the CeA of Sprague-Dawley rats (Liu et al , 2004; Varodayan et al , 2017) and C57BL/6 mice (Silberman et al , 2013a). In Wistar rats, CRF application had divergent effects on glutamatergic signaling, with a subset of CeA neurons exhibiting enhanced glutamate release following exogenous CRF application and a subset exhibiting reductions in glutamate release (Herman et al , 2016c).…”
Section: Crf and Amygdala Microcircuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…CRF has also been shown to alter excitatory transmission within the CeA. CRF application reduced evoked glutamate responses and enhanced glutamate release in the CeA of Sprague-Dawley rats (Liu et al , 2004; Varodayan et al , 2017) and C57BL/6 mice (Silberman et al , 2013a). In Wistar rats, CRF application had divergent effects on glutamatergic signaling, with a subset of CeA neurons exhibiting enhanced glutamate release following exogenous CRF application and a subset exhibiting reductions in glutamate release (Herman et al , 2016c).…”
Section: Crf and Amygdala Microcircuitrymentioning
confidence: 99%
“…The CRF1 receptor also plays a role in the effects of acute alcohol on excitatory synaptic transmission in the CeA. Several studies (Herman et al , 2016c; Silberman et al , 2015; Silberman et al , 2013b; Varodayan et al , 2017) have shown that acute alcohol can potentiate spontaneous glutamatergic EPSCs in the CeA. This potentiation was blocked by pretreatment with a CRF1 receptor antagonist, but persisted despite the ablation of CRF-containing neurons in the CeA and whole organism (Silberman et al , 2015).…”
Section: Alcohol and The Crf1 Systemmentioning
confidence: 99%
“…Alcohol’s effects on male neurons of the medial CeA have been extensively studied. Alcohol enhances GABAergic inhibitory postsynaptic responses and reduces the magnitude of glutamatergic excitatory postsynaptic potentials and currents (EPSP/Cs) (Roberto et al, 2006; Roberto, Madamba, Moore, Tallent, & Siggins, 2003; Roberto, Madamba, Stouffer, Parsons, & Siggins, 2004), in part via CRF’s actions (Bajo, Cruz, Siggins, Messing, & Roberto, 2008; Herman et al, 2013; Herman et al, 2016; Varodayan et al, 2017). Given the aforementioned sex differences in the effects of stress and alcohol on CeA CRF neurons, associated changes in neuronal activity would be expected to display different patterns in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…We also characterized Fos‐positive neurons after exposure to the UCS in the amygdala by colabeling Fos and glutamatergic marker, CamKinaseII (Figure E,F), as the BLA contains a majority (~80%) of glutamatergic neurons while the CeA contains mainly (~95%) γ‐aminobutyric acid (GABA) neurons . We found that the percentages of neurons that were colabeled for Fos and CaMKII were 80.4 ± 2.3 in the BLA and 3.3 ± 2.7 in the CeA, indicating that exposure to the UCS activates a majority of glutamatergic neurons in the BLA.…”
Section: Resultsmentioning
confidence: 98%